Flourishing and its influencing factors among maintenance hemodialysis patients in Shanghai, China: a cross-sectional study - Zeng, Xiao Qing; Yan, Hong Li; Qian, Yue Qin; Li, Yong Qi; Yang, Jie; Gong, Yan Lin; Liu, Yi; Chen, Li Jing; Wu, Jing; Chu, Jing (Frontiers in Psychiatry, 2025)
BackgroundMaintenance hemodialysis (MHD) patients face substantial psychological challenges that impacting their overall quality of life. Flourishing, a concept within positive psychology, refers to a state of mental well-being and personal growth. Despite its importance, the factors influencing flourishing in MHD patients remain underexplored.AimThis cross-sectional study aimed to assess flourishing levels among MHD patients in Shanghai, China, and identify sociodemographic, disease-related, and psychological factors associated with flourishing, with implications for targeted interventions.MethodFrom October to November 2022, 376 MHD patients across four hospitals completed validated scales measuring flourishing (PERMA Profiler), personality traits (TIPI-C), regulatory emotional self-efficacy (RES), perceived social support (PSSS), and quality of life (EQ-5D). Statistical analyses, including regression analysis, were used to identify factors associated with flourishing.ResultsThe mean flourishing score was 6.28 ± 1.763, indicating moderate levels compared to general populations. Full-time employment (β = 0.749, p = 0.033), retirement (β = 0.675, p = 0.043), social support from friends/others (β = 0.039, p < 0.001), conscientiousness (β = 0.133, p < 0.001), and better quality of life (β = 1.281, p = 0.001) emerged as significant positive predictors. Conversely, longer dialysis duration (ρ = -0.135, p = 0.009) and higher perceived disease impact (β = -0.084, p = 0.268) were negatively associated with flourishing.ConclusionsThe findings highlight the complex interplay between sociodemographic, disease-related, and psychological factors in influencing the flourishing of MHD patients. The level of flourishing in MHD patients’ needs to be improved. Developing targeted interventions based on these relevant factors improves quality of life and thus contributes significantly to the well-being of MHD patients.